Gestational SARS-CoV-2 infection is associated with placental expression of immune and trophoblast genes. (August 2022) - Lesseur, Corina; Jessel, Rebecca H.; Ohrn, Sophie; Ma, Yula; Li, Qian; Dekio, Fumiko; Brody, Rachel I.; Wetmur, James G.; Gigase, Frederieke A.J.; Lieber, Molly; Lieb, Whitney; Lynch, Jezelle; et al.
Abstract: Introduction: Maternal SARS-CoV-2 infection during pregnancy is associated with adverse pregnancy outcomes and can have effects on the placenta, even in the absence of severe disease or vertical transmission to the fetus. This study aimed to evaluate histopathologic and molecular effects in the placenta after SARS-CoV-2 infection during pregnancy. Methods: We performed a study of 45 pregnant participants from the Generation C prospective cohort study at the Mount Sinai Health System in New York City. We compared histologic features and the expression of 48 immune and trophoblast genes in placentas delivered from 15 SARS-CoV-2 IgG antibody positive and 30 IgG SARS-CoV-2 antibody negative mothers. Statistical analyses were performed using Fisher's exact tests, Spearman correlations and linear regression models. Results: The median gestational age at the time of SARS-CoV-2 IgG serology test was 35 weeks. Two of the IgG positive participants also had a positive RT-PCR nasal swab at delivery. 82.2% of the infants were delivered at term (≥37 weeks), and gestational age at delivery did not differ between the SARS-CoV-2 antibody positive and negative groups. No significant differences were detected between the groups in placental histopathology features. Differential expression analyses revealed decreased expression of two trophoblast genes ( PSG3 and CGB3 ) and increased expression of three immune genes ( CXCL10, TLR3 and DDX58 ) in placentas delivered from SARS-CoV-2 IgG positive participants. Discussion: SARS-CoV-2 infection during pregnancy is associated with gene expression changes of immune and trophoblast genes in the placenta at birth which could potentially contribute to long-term health effects in the offspring. Highlights: No differences detected in gestational age at delivery or placental pathology. SARS-CoV-2 associated with lower placental gene expression of PSG3 and CGB3. SARS-CoV-2 associated with higher placental gene expression of CXCL10, TLR3 and DDX58.